MASTER-ABSCHLUSS AUS DER STELLUNG DER PRAXIS - Криловець, М. Г. (Pedagogy of Higher and Secondary Education, 2011)
Future Geography Teachers preparedness for research work is defined as a speciality competence characterized by the skills: to do research study, to collect and analyze research information, to have a good command of methodology apparatus of research, to have a good command of theoretical, empirical, statistical and other research methods, to determine the resultativeness of research work, to put the results of the research into teaching.